Input-Output Modelling in the MENA Region - A case study for Morocco - Britta Stöver; Kirsten S. Wiebe; Ulrike Lehr; Marc I. Wolter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2012)
Science-based policy analysis becomes increasingly important in the globalised world. Complex economic and social structures need to be thoroughly analysed and direct and indirect effects of policy measures should be identified and, if possible, quantified. Economic policy modelling has a long tradition (Almon, 1991) and economic models have over the past decades become more detailed regarding the economic structure and more extensive regarding the non-economic aspects represented in these models. There exist detailed structural economic models for most OECD countries. For newly emerging economies and developing countries only few such models exist. A global database and model environment is provided by the GTAP project, which is frequently used to develop computable general equilibrium (CGE) models. These models use a unique database, which often is not compatible to datasets of national statistic offices. Still, there are countries for which no such structural economic models exist. The macro-economic PRESIMO model for Morocco for example does not include the industry structure of the Moroccan economy. However, analyses at the industry level are important when analysing the development of for example labour markets or energy demand. The economic opportunities from international projects such as DESERTEC (Concentrating Solar Power in the Saharan Region) could be evaluated identifying sectors, which benefit the most. Using the example of Morocco this paper outlines the prerequisites for developing structural economic models and shows application possibilities of these models for simulating the effects of policy measures.
Keywords: O21; 330; Input-Output modelling; policy analysis; application possibilities; Wirtschaftsmodell; Wirtschaftsstruktur; Input-Output-Analyse; Marokko